Geomagnetically Induced Currents and Harmonic Distortion: Storm‐Time Observations From New Zealand. Issue 3 (13th March 2020) - Rodger, Craig J.; Clilverd, Mark A.; Mac Manus, Daniel H.; Martin, Ian; Dalzell, Michael; Brundell, James B.; Divett, Tim; Thomson, Neil R.; Petersen, Tanja; Obana, Yuki; Watson, Neville R.
Abstract: Large geomagnetic storms are a known space weather hazard to power transmission networks due to the effects of geomagnetically induced currents (GICs). However, research in this area has been hampered by a lack of GIC observations. Previous studies have noted that New Zealand is unusually fortunate in having a comparatively dense, high quality, set of GIC measurements, spanning >60 transformers in >20 substations. However, due to operational reasons these observations are clustered in the mid and lower South Island. In this paper we analyze space weather‐induced GIC impact patterns over the entire country by using a different set of sensors that monitor levels of harmonic distortion, with even and odd harmonics measured separately. GICs lead to half cycle transformer saturation and is one of the few ways in which even harmonics are produced in a well‐run power transmission network. We make use of harmonic distortion measurements at 377 circuit breakers made at 126 separate locations. Focusing on the intense geomagnetic storm activity during 6–9 September 2017, we show how the even harmonic distortion observations provide a useful new picture of GIC‐stressed transformers. These observations demonstrate how GIC effects can be monitored by using even harmonic distortion in locations where no GIC measurements are present (e.g., the most of the North Island). We understand that harmonic distortion measurements are fairly common in electrical networks and could provide a new tool for space weather researchers. Key Points: Harmonic distortion measurements made at 126 locations in New Zealand are used to locate stressed transformers during geomagnetic storms Geomagnetically induced current effects on transformers can be identified through commonly measured even harmonic distortion data Even harmonic distortion is observed in unexpectedly low latitude locations during the 6–9 September 2017 geomagnetic storm period